Delivering Elder- and Community-Led Aboriginal Early Childhood Development Research: Lessons from the Ngulluk Koolunga Ngulluk Koort Project - Brad M. Farrant; Carrington C. J. Shepherd; Carol Michie; Clair Scrine; Michael Wright; Nicole Ilich; Tanya Jones; Glenn Pearson (MDPI AG, 2019)
Elder- and community-led research processes are increasingly being acknowledged as critical for successful Aboriginal health and wellbeing research. This article provides an overview of the methodologies, methods and progress of the Ngulluk Koolunga Ngulluk Koort (Our Children, Our Heart) project—an Elder- and community-led research and research-translation project focused on the early childhood development of Australian Aboriginal children in an urban context (Perth, Western Australia). We describe the application of a participatory action research methodology that is grounded in Aboriginal worldview(s), from the collaborative development of the original idea to the post-funding processes of co-design and implementation, data collection, analysis, interpretation and translation.